Double Parathyroid Adenoma Presenting as One Mass: A Case Report - Petruokaitė, Rugilė; Eismontas, Vitalijus; Samalavičius, Narimantas Evaldas (Acta medica Lituanica, 2024)
Background and Objectives: Primary hyperparathyroidism is a common endocrinological condition, which is usually caused by solitary parathyroid adenoma. The aim of this article is to present a case of double adenoma presenting as one and literature review on this topic.Case presentation: 56 years old female suffering from generalized fatigue, bone pain, unstable body weight and palpitations was diagnosed with primary hyperparathyroidism. Further investigation revealed elevated parathyroid hormone (PTH), ionized and total calcium levels. Imaging showed two adenomas merging into one. Parathyroidectomy was performed and final intraoperative PTH (IOPTH) decreased by 71.6%. Parathyroid adenoma measuring 40 mm x 15 mm x 11 mm and weighing 1 g 483 mg was excised. 7 weeks after surgery patient was feeling well but her PTH level was elevated again.Conclusions: As far as we know, the double parathyroid adenoma presented in this case report is the largest reported in the Northern Europe and the first one that presents as one mass within the region. Double adenoma increases the risk of recurrent primary hyperparathyroidism (PHPT) and requires more careful and longer follow up after surgery than solitary adenomas. Final IOPTH must decrease by at least 50% within 10 minutes. This case shows that despite final IOPTH drop by more than 50%, after few weeks normocalcemic elevated parathyroid hormone (NCePTH) phenomenon was noticed. This phenomenon does not indicate surgical failure.
Keywords: double parathyroid adenoma; primary hyperparathyroidism; parathyroidectomy